The influence of mindset abstraction on preference for mixed versus extreme approaches to multigoal pursuits. Issue 1 (5th May 2022) - Lu, Fang‐Chi; Park, Jooyoung; Nayakankuppam, Dhananjay
Abstract: Facing multiple conflicting goals, consumers may attempt to simultaneously pursue multiple goals by choosing mixed vice–virtue bundles in each consumption episode (mixed approach). Alternatively, they may maximize their pursuit of one goal at a time and sequentially manage multiple goals by alternating between pure‐virtue and pure‐vice bundles across consumption episodes (extreme approach). The current research proposes that consumer preferences between the two approaches depend on mindset abstraction. Across four experimental studies in the domains of food and financial decision‐making, we demonstrate that, relative to an abstract mindset, a concrete mindset increases preference for the extreme approach over the mixed approach. Furthermore, by observing actual food choices over a seven‐day period, this research provides a comprehensive picture of how a chronic mindset relates to multigoal management in long‐term consumption patterns. The findings have both theoretical implications for the goal literature and managerial implications for marketers and policymakers.